The education impacts of cash transfers for children with multiple indicators of vulnerability - Evans, David K.; Gale, Charles; Kosec, Katrina (Center for Global Development, 2020)
As more countries approach universal primary school enrollment, the remaining children out of school merit special attention. Multiple studies have demonstrated that cash transfers boost educational outcomes for children on average, but do children with multiple indicators of vulnerability benefit from these safety net programs? This study draws on a randomly assigned pilot of a community implemented cash transfer program targeted to households with low socioeconomic status in Tanzania to examine the educational impacts of cash transfers for children facing different challenges. We find that on average, being assigned to receive cash transfers significantly boosts children’s school participation (between 8 and 10 percentage points) and primary completion rates (between 14 and 16 percentage points). But we provide suggestive evidence that these gains are unequally distributed across children. The poorest children in our sample are more likely to experience gains along the extensive margin (i.e., higher likelihood of ever attending school), whereas the less poor children are more likely to experience gains along the intensive margin (i.e., higher likelihood of primary school completion). Girls and boys benefit approximately equally. Finally, educational gains are concentrated among students who were performing better in school at baseline. Cash transfers benefit vulnerable children, but they do not benefit all vulnerable children equally, nor in the same ways.